SAWING PATTERNS FOR THE BREAKDOWN OF Pinus caribaea var. caribaea WOOD ON PORTABLE SAWMILLS - Carreiro, Gean David; Silva, Pedro Ygor Correia da Silva e; Mulin, Lucas Braga; Silva, João Gabriel Missia da; Oliveira, Michel Picanço; Moulin, Jordão Cabral (Floresta, 2021)
The aim was to assess the effect of sawing patterns on lumber yield, energy consumption, and surface quality of Pinus caribaea var. caribaea wood sawn on a portable sawmill. The logs had an average diameter of 29 cm, length of 3 m, and age of 46 years. A specific sawing pattern was used for the production of cants and boards and another for two-sided cants, obtained after a subsequent edging operation. Log and board volumes were determined, and the ratio of these variables was used to calculate the lumber yield. The amount of energy used during breakdown was determined by measuring the electric current applied and time of execution of the process. Surface quality was assessed by the glass microsphere method, according to technical standards. Lumber yield ranged from 48 to 53%, considered satisfactory. Lumber yield and energy consumption were lower with the cant sawing pattern. Board surface quality was not influenced by sawing pattern, with all boards having fine to very fine surface textures. Energy consumption and board surface quality were not influenced by cutting position. Although the cant sawing pattern provided a lower lumber yield, the energy savings associated with the absence of edging operations may make it attractive for small lumber producers. However, this decision should be based on an economic analysis and take into account the market value of the wood to be processed.